Pengaruh Online Custemer Review Dan Rating Terhadap Keputusan Pembelian Produk Hijab Umamam Pada Marketplace Shopee (Studi Kasus Masyarakat Kp. Rumbia Rt 001/Rw 003 Desa Karang Patri) - Pangseti, Salamah Puji; Ramdayani, Rani (STIE AMKOP, 2024)
This study aims to determine the Influence of Online Customer Review and Rating on the Purchase Decision of Umama Hijab Products on the Shopee Marketplace. This study uses a quantitative method. The population in the study was 135 and the sample was 101 respondents. The data collection technique used in this study used a questionnaire and observation which were tested for Validity and Reliability. The data analysis technique for this study used the Classical Assumption Test, Multiple Linear Regression, Hypothesis Testing (t-Test and f-Test) and the Coefficient of Determination. Based on the results of this study, it shows that Online Customer Review has a positive and significant influence on the Purchase Decision of Umama Hijab Products on the Shopee Marketplace, partially Rating has a positive and significant influence on the Purchase Decision of Umama Hijab Products on the Shopee Marketplace, simultaneously Online Customer Review and Rating have a positive and significant influence on the Purchase Decision of Umama Hijab Products on the Shopee Marketplace. The Determination Coefficient value of 70.5% shows the contribution of Online Customer Review and Rating to the purchase decision of Umama Hijab Products on the Shopee Marketplace and the remaining 29.5%.